العولمة وأثرها في تعليم اللغة العربية للناطقين بغيرها - الربابعة، إبراهيم حسن (الجامعة الأردنية - عمادة البحث العلمي, 2018)
The study aims at exploring new horizons of researching the phenomenon of globalization and its effect on teaching Arabic Language as a second language. It also attempts to stimulate new ideas to reorganize the priorities and outcomes of this research in order to overlook the historical perspective that abused the conventions of globalization in different forms of life. Some of these dimensions are the concept and emergence of globalization, exploring the condition of Arabic language and its position among other languages and the challenges that it faces, and observing the significance of Globalization and its effects on teaching Arabic as a second language.
هدفت الدراسة إلى استشراف آفاق جديدة للبحث عن ظاهرة العولمة وأثرها في تعليم اللغة العربية للناطقين بغيرها، واستثارة أفكار أبكار لإعادة تنظيم أولويات هذا البحث ومخرجاته، وتجاوز النظرة التاريخية التي استبدت بمقاليد العولمة وآثارها في مجالات الحياة، ومن هذه الآفاق أو حديث الأفكار مفهوم العولمة ونشأتها، واستعراض واقع اللغة العربية ومكانتها بين اللغات الأخرى والتحديات التي تواجهها، فضلا عن رصد تجليات العولمة وأثرها في تعليم اللغة العربية للناطقين بغيرها.
Keywords: العولمة -- اللغة العربية -- تعليم اللغة العربية للناطقين بغيرها